Prodajna in marketinška usmeritev podjetij - Zupančič, Melita (Akademija MM, 1998)
The research proves, that for the Slovene businesses it is still not valid that in order to achieve business success the acceptance of necessary. We have ascertained, that even the most profitable Slovene businesses do not differentiate well between marketing and selling; in their management the selling orientation is still very much present.
Keywords: corporation; marketing; podjetje; prodaja; strategija trženja; trženje